A CASE REPORT: A SCROTAL FLAP FOR PENILE PARAFFINOMA RECONSTRUCTION - Iswara, Rr. Theodora Ratih Labdagati; Ul Hakim, Muhammad Aulia; Malineni, Jahnavi; Hidalgo, Katrina Ysabelle (Jurnal Rekonstruksi dan Estetik, 2023)
Highlights: The single-stage scrotal flap technique can be used for paraffinoma cases where the lesion does not involve the scrotum. The therapy addresses concerns related to restoring the penile function as a sexual organ with the best appearance. The V-Y plasty can be used not only to form the penile shaft but also to minimize penile shortening. Abstract: Introduction: A large penile size is a source of pride and a symbol of masculinity for many men. One commonly used alternative for penile enlargement is the injection of high-viscosity liquids, such as paraffin, silicone, vaseline, and other substances, into the penis. However, this procedure can lead to negative consequences, including paraffinoma and siliconoma, which can cause pain during erections and even a reduction in penile size. Case Illustration: A 29-year-old male presented with complaints of penile enlargement, hardness on palpation, and pain during erections for the past three months before admission to the hospital. The patient's social history revealed that one year before admission, he had undergone a paraffin injection on the penile shaft, which was performed by non-medical personnel. Physical examination revealed a circumferentially enlarged penile shaft that was hard on palpation. A wide excision of the fibrotic tissue on the penile shaft was performed, and a scrotal flap was used to cover the exposed area. Discussion: We performed a wide excision of the fibrotic tissue on the penile shaft and followed it with a V-Y scrotal flap procedure to cover the exposed area. This single-stage surgery was feasible because the scrotal skin was still healthy and suitable for defect coverage. Conclusion: Penile reconstruction surgery with a scrotal flap is one of the therapeutic options for addressing paraffinoma cases, offering both cosmetic and functional benefits.